EVALUASI DAMPAK PENERAPAN SISTEM INFORMASI KEPEGAWAIAN (SIKAWAN) TERHADAP KINERJA SDM DI RSUD KABUPATEN JOMBANG - Hudan Eka Rosyadi; Iqbal Baghis Kenvin (Universitas Islam Balitar, 2026)
The implementation of the Employee Information System (SIKAWAN) at Jombang Regional General Hospital (RSUD) aims to enhance administrative efficiency and employee performance. However, challenges arise due to the dominance of Baby Boomer, Gen X, and Gen Y employees who are less familiar with technology, coupled with limited IT resources for user support. This study analyzes the system’s acceptance and its impact on employee performance using the Technology Acceptance Model (TAM), given that the system is still in the development phase and requires comprehensive evaluation. This research aims to measure the effectiveness of SIKAWAN in improving employee performance at RSUD Jombang based on technology acceptance factors, including Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), and Behavioral Intention (BIU). This quantitative study employed a Likert-scale questionnaire distributed to 100 RSUD Jombang employees. Data were analyzed using TAM through validity and reliability tests, multiple linear regression, and classical assumption tests (normality, multicollinearity, heteroscedasticity) with SPSS software. The analysis revealed that Perceived Usefulness (β=0.394; p=0.000) and Behavioral Intention (β=0.374; p=0.000) significantly influenced Actual System Usage (AU). However, Perceived Ease of Use (β=0.063; p=0.460) and Attitude Toward Using (β=-0.098; p=0.253) showed no significant impact. The simultaneous test (F=36.040; p=0.000) confirmed the TAM model’s validity in explaining system acceptance. SIKAWAN’s effectiveness is driven by users’ perception of its benefits and sustained usage intention, rather than ease of operation. To enhance employee performance, intensive socialization about system benefits, age-specific training for Baby Boomers, and improvements in system interface and stability are recommended. The findings emphasize integrating user psychological factors into public sector HR information system development.